Choice19 : Nineteen contemporary Czechoslovak photographers. - Watriss, Wendy; Baldwin, Frederik C; Dufek, Antonin; Fotofest Houston (Prague : Art Centrum, 1990)
Banka, Pavel ; bárta, Jaroslav ; Grygar, Stephan ; Hanka, Jiri ; Holomicek, Bohdan ; Kolar, Viktor ; Lhoták, Zdenek ; Lutterer, Ivan ; Machotka, Miroslav ; Malý, Jan ; et al.
Fotofest Houston, Texas
kunstcatalogus
Keywords: Tsjechoslowakije